Design and development of a puzzle platformer game - Xie, Shuohao (Nanyang Technological University, 2024)
This report describes my journey in creating a 2.5D single-player platform game with my team. Our game is special because it combines puzzles that players must solve to move forward and proceed to next levels. We chose a low poly as our art style for our graphics, which means the game has a simple but attractive look. We built the game using the Unity 3D, which helped us make our ideas come to life. Our main reason for making this game was to give players an immersive gaming experience and reward players some of mental achievements by solving puzzles. We think games are a great way to learn problem-solving skills, and our game aims to do achieve that in a fun and engaging way. This report aims to provide insight into the creative and technical efforts required to bring our game from idea to reality, emphasizing the importance of design in crafting an engaging and thought-provoking game.